PENERAPAN IRIGASI PADI HEMAT AIR (IPHA) DAN PEMUPUKAN UNTUK MENINGKATKAN PRODUKTIVITAS PADI SAWAH VARIETAS UNGGUL: Penerapan Irigasi Padi Hemat Air (IPHA) - Pramono, Eko; Hadi , Muhammad Syamsoel; Kamal, Muhammad; Setiawan, Kukuh (Agriculture Faculty, Universitas Lampung, 2025)
The Agricultural Introduction Program (P3) was held for the third time in Argopeni Village, Sumberejo District, Tanggamus Regency, Lampung Province on February 1-8, 2025. Farmers raised the issue of how to increase rice productivity in this village. This extension activity aims to increase farmers' knowledge about the application of water-saving rice irrigation techniques (IPHA) and fertilization to increase the productivity of superior rice varieties. The IPHA method was developed by the Ministry of Public Works, Directorate General of Water Resources, to save water and increase rice productivity. With lectures and discussions on the topic, rice farmers can understand the application of water-saving rice irrigation methods (IPHA) which are also combined with fertilizer applications.